BURNOUT PADA PERAWAT DITINJAU DARI EFIKASI DIRI DAN DUKUNGAN SOSIAL - Lailani, Fereshti (TALENTA, 2012)
The study was meant to know the relationship between self-efficacyand social support with burnout among nurses. Proposed hypotheses were asfollowed: 1) burnout correlated with self-efficacy dan social support; 2) selfefficacynegatively correlated with burnout, the lower self-efficacy was, thehigher was the burnout; 3) social support negatively correlated with burnout, thehigher social support was, the lower was the burnout. Te subject of the study consisted of 97 nurses of PKU MuhammadiyahHospital at Jogjakarta. Data was collected through questionnaire method usingburnout, self-efficacy and social support scales. Statistical method usedregression analysis with SPSS for Windows and SPS-2000 of Sutrisno Hadi. The results showed that: 1) there was significant correlation betweenself-efficacy and social support with burnout ( R= 0.784, F= 75.005, p < 0.01)and it contributed as much as 61.5 % ; 2) self-efficacy had significantly negativecorrelation with burnout ( r= - 0.289, t= - 2.923, p < 0.01) and it contributed asmuch as 22.307 % ; 3) social support correlated significantly with burnout(r= - 0.448, t= - 4.852 , p < 0.01) and it contributed as much as 39.169 %.